2011
DOI: 10.7326/0003-4819-154-1-201101040-00289
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Dabigatran Compared With Warfarin for Stroke Prevention in Atrial Fibrillation

Abstract: American Heart Association and Veterans Affairs Health Services Research & Development Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
303
2
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(326 citation statements)
references
References 59 publications
11
303
2
10
Order By: Relevance
“…The current finding is consistent with previously reported cost-effectiveness analyses of dabigatran versus warfarin, in which the ICER of dabigatran would increase as its utility score decreased. 13,47 The three-way sensitivity analysis explored the interaction of two cost-driving factors (monthly cost of NOACs and increment in monthly cost of anticoagulation service), as well as different levels of INR control on the cost-effectiveness of warfarin and NOACs. The results showed that at no increment in monthly service cost, warfarin therapy would be the costeffective option at TTR 60 %, 70 % and 75 % if the monthly drug cost of NOACs was >USD 200, >USD 122 and >USD 85, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current finding is consistent with previously reported cost-effectiveness analyses of dabigatran versus warfarin, in which the ICER of dabigatran would increase as its utility score decreased. 13,47 The three-way sensitivity analysis explored the interaction of two cost-driving factors (monthly cost of NOACs and increment in monthly cost of anticoagulation service), as well as different levels of INR control on the cost-effectiveness of warfarin and NOACs. The results showed that at no increment in monthly service cost, warfarin therapy would be the costeffective option at TTR 60 %, 70 % and 75 % if the monthly drug cost of NOACs was >USD 200, >USD 122 and >USD 85, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The costeffectiveness analyses based upon the treatment outcomes of these trials reported that NOACs were more costeffective than warfarin when anticoagulation control was suboptimal. [11][12][13][14][15][16][17] For anticoagulation centers with average TTR of 60 % or below, the possible options are either the use of more expensive NOACs, or providing additional resources to improve TTR. Various therapeutic strategies to improve TTR have been examined and the findings suggest that employment of a clinical factor-guided dosing algorithm, 18 frequent INR monitoring, [19][20][21] and management of anticoagulation care by specialists in the use of anticoagulants 22,23 are effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Another big issue is the high cost of these drugs that, on the basis of the prices for licensed indications, is unlikely to be lower than €2-3 per day. Although in an economic analysis using data from the RE-LY (Randomized Evaluation of Long-Term Anticoagulation Therapy) trial [60], dabigatran was estimated to be cost-effective compared to warfarin in patients with atrial fibrillation at high risk of stroke, their cost-effectiveness in a relatively short period of time (such as that encompassing most VTE treatments) is yet to be proven.…”
Section: Resultsmentioning
confidence: 99%
“…13 be shown. 21 However, for a condition that requires long-term prophylaxis there are no long-term data to suggest that they will be safe and effective alternatives. The Watchman device is delivered by catheter to the left atrial appendage.…”
Section: Alternative Oral Anticoagulantsmentioning
confidence: 99%